Tajikistan : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Against the backdrop of a serious deterioration in its terms of trade and a large reversal of private capital flows following the Russian crisis in August 1998, the Tajik economy has entered a period of adjustment. Output growth has slowed down, inflation has flared up, and the exchange rate has weakened. More recently, macroeconomic stability has restored as the authorities have embarked on a strong adjustment path in response to adverse external developments and to correct the slippages in policy implementation during 1999.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet